Analisis Pembelajaran Kooperatif Tipe Make A Match Pada Siswa Kelas IV A SDIKT Robbi Rodhiya - Muhammad Zaky Sya'bani; Nurkholis (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2022)
This research goes from the application of the make a match method in the learning process which is based on the low results of learning Arabic students. It is caused by lack of activeness of students in learning Arabic, use of less effective methods so that students still struggle and feel saturated in Arabic lessons. The purpose of this research is to analyze the use of make a match learning model in improving students' Arabic learning outcomes, The subject of this research is class IV-A students of SDIKT Robbi Rodhiya Bandar Lampung totaling 30 students and implemented in 3 cycles. Based on the results of research that has been carried out then the conclusion was reached that there was an increase in student Arabic learning outcomes in each cycle. In cycle 1 obtained an average value of 67 with a percentage increase of 26.67%, in cycle 2 to 71.5 with a percentage increase of 70% and in cycle 3 increased back to 75.30 with an 80% percentage increase. Based on these results it can be concluded that using a make a match learning model can improve Arabic learning outcomes of grade IV-A students of SDIKT Robbi Rodhiya